Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021 - Sekar Fitri Tengah Panuluh; Firdaus Firdaus; Suwardi Suwardi; Sherly Vera Ari Sabrina; Devanya Sonia Aulia Devi; Endah Ratnasari; Shafiyah Ainur Rafi'ah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the effect of Profitability, Liquidity, and Company Size on Firm Value. The independent variable is Profitability as measured by Return On Assets, Liquidity measured by the Current Ratio, and the size of the company which is measured by Size, while the dependent variable is the value of the company which is measured by using Price To Book Value. The approach used in this research is a quantitative approach. The population in this study are all food and beverage sub-sector companies listed on the Indonesian stock exchange in 2018-2021. The sample in this study was obtained using a purposive sampling method so that a sample of 19 companies was obtained with a total of 65 data. The analysis technique used is multiple linear regression analysis using SPSS version 25 as a tool in the calculation. The results of this study indicate that Profitability has a positive and significant effect on Firm Value with a p-value significance of 0.019 (<0.05). Liquidity has no significant negative effect on firm value with a p-value of 0.268 (> 0.05). Firm size has a positive and significant effect on firm value with a p-value of 0.009 (<0.05). Together based on simultaneous tests of Profitability, Liquidity, and Firm Size have a positive and significant effect on Firm Value.